2014
DOI: 10.1039/c4cp03986f
|View full text |Cite
|
Sign up to set email alerts
|

The structural and energetic aspects of substrate binding and the mechanism of action of the DapE-encoded N-succinyl-l,l-diaminopimelic acid desuccinylase (DapE) investigated using a hybrid QM/MM method

Abstract: With increasing cases of fatal bacterial infections and growing antibiotic resistance, unrelenting efforts are necessary for identification of novel antibiotic targets and new drug molecules. The dapE-encoded N-succinyl-L,L-diaminopimelic acid desuccinylase (DapE) is a di-nuclear Zn containing enzyme in the lysine biosynthetic pathway which is indispensable for bacterial survival and absent in the human host, thus a potential antibiotic target. The DapE enzyme catalyzes the hydrolysis of N-succinyl-L,L-diamino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 65 publications
5
44
0
Order By: Relevance
“…All residues with atoms within 15 from Fe were allowed to optimize their geometry,w hereas coordinates of the remaining part of the system were fixed (see Figure S1 in the Supporting Information). Previous works have shown that mechanical embedding with ac harge-update scheme converges very quickly [56] and yields reaction-energy profiles very similar to those obtained with electronic embedding. Twob asis sets were employed:t he lacvp basis (BS1) for most optimisations, frequency and ESP calculations and ab asis set that combined the lacv3p + basis set for the metal ion with 6-311G(d,p) basis set for all other atoms (BS2).…”
Section: Epr Spectroscopymentioning
confidence: 59%
See 1 more Smart Citation
“…All residues with atoms within 15 from Fe were allowed to optimize their geometry,w hereas coordinates of the remaining part of the system were fixed (see Figure S1 in the Supporting Information). Previous works have shown that mechanical embedding with ac harge-update scheme converges very quickly [56] and yields reaction-energy profiles very similar to those obtained with electronic embedding. Twob asis sets were employed:t he lacvp basis (BS1) for most optimisations, frequency and ESP calculations and ab asis set that combined the lacv3p + basis set for the metal ion with 6-311G(d,p) basis set for all other atoms (BS2).…”
Section: Epr Spectroscopymentioning
confidence: 59%
“…Finally, the geometry was reoptimised with the new set of QM charges. Previous works have shown that mechanical embedding with a charge‐update scheme converges very quickly and yields reaction‐energy profiles very similar to those obtained with electronic embedding . A D3(BJ) van der Waals correction was computed for the QM region with the DFTD3 program .…”
Section: Methodsmentioning
confidence: 99%
“…The amide carbonyl of l , l -SDAP is positioned near Zn2, while the amide N–H acts as a hydrogen bond donor to the backbone carbonyl of Thr325.A, a residue that was previously implicated as being catalytically important. 37 In addition, His194.B moves into the active site and forms an oxyanion hole along with Zn2, via a strong hydrogen bonding interaction with the amide carbonyl oxygen, O2. The proximal carboxylate of l , l -SDAP participates in bifurcated hydrogen bonds with side chains Arg258.A, Thr325.A, and Asn245.B (Figure 8B).…”
Section: Resultsmentioning
confidence: 99%
“…ELAC is implemented in the ONIOM software, but in practice it gives often severe convergence problems and is therefore seldom used. Instead, alternative approaches have been implemented, based on iterative calculations with mechanical embedding and updated charges (Kawatsu et al, 2011 ; Dutta and Mishra, 2014 ; Wójcik et al, 2014 ). It could therefore be recommended that ONIOM implements electrostatic embedding with only VLAC, which is a very stable approach in ComQum.…”
Section: Discussionmentioning
confidence: 99%